Impact of construction waste minimization at construction site: Case study - Umar, U.A. (Penerbit UTM Press, 2016)
Waste reduction in the construction sector is essential not just from the position of overall performance, but also interests escalated recently about the detrimental impact of the waste of construction materials on the natural surroundings. The reuse and recycling of construction elements used to be substantial due to material scarcity during the war and post-war era, specifically when the price of virgin materials keep inflating. Nevertheless, the motivation to reuse and recycle construction materials has fallen ever since the flow of raw materials has grown more consistent and satisfactorily. This paper involves an ongoing sequence of waste audits at Universiti Teknologi Petronas (UTP) R&D construction sites. The methodology consists of discussion, observation and quantitative evaluations of the kinds and distribution of wastes. The finding of this study demonstrates that the project aimed at both minimizing the volume of waste generated and diverting as much waste as possible from landfill that contribute to the recycle with over 1200 tonnes of material which constitute about 73 of recycle and reused rate mainly from timber and metal. Â© 2016 Penerbit UTM Press. All rights reserved.